Network architecture and regulatory logic in neural crest development - Hovland, Austin (Wiley Interdiscip Rev Syst Biol Med, 2019)
The neural crest is an ectodermal cell population that gives rise to over thirty cell types during vertebrate embryogenesis. These stem cells are formed at the border of the developing central nervous system and undergo extensive migration before differentiating into components of multiple tissues and organs. Neural crest formation and differentiation is a multi-step process, as these cells transition through sequential regulatory states before adopting their adult phenotype. Such changes are governed by a complex gene regulatory network (GRN) that integrates environmental and cell-intrinsic inputs to regulate cell identity. Studies of neural crest cells in a variety of vertebrate models have elucidated the function and regulation of dozens of the molecular players that are part of this network. The neural crest GRN has served as a platform to explore the molecular control of multipotency, cell differentiation, and the evolution of vertebrates. In this review, we employ this genetic program as a stepping-stone to explore the architecture and the regulatory principles of developmental GRNs. We also discuss how modern genomic approaches can further expand our understanding of genetic networks in this system and others.